‘Resources for Infrastructures Deals’ in Africa: Analysis of Chinese Companies Operations in Extractive Industries in Uganda. - Ogwang, Tom; Vanclay, Frank (Department of Cultural Geography, Faculty of Spatial Sciences, University of Groningen, 2012)
The discovery of commercially viable oil deposits in 2006 in Uganda raised hopes that the enormous revenues expected to accrue would make poverty history (Bainemugisha et al, 2006). At the same time, however, the discovery has generated fear that the oil resources would turn out to be a curse rather than a blessing, especially if the anticipated revenues were not properly planned for and, more importantly, equitably and transparently utilized (Masiko, 2006). The discovery has also seen multiple players in the extractive industries coming to get a share in the industry. If poorly managed, Uganda will join the list of ‘resource curse’ countries which will erode the achievements made in the past and plunge the country into armed conflict and instability. Therefore, the research question to be explored in this paper is: “How does the Chinese companies and their concept of ‘Resources for Infrastructures deals’ in Africa in the extractive industries benefit those countries and vice versa?
Analysis of Chinese Companies Operations in Extractive Industries in Uganda.
Keywords: Resources, infrastructure, east, west, business models